Physichochemical charactheristics and organoleptics of Chayote leather in various sugar and CMC concentration - Bekti K, Endang; Haryati, Sri; Putri, Aldila Sagitaning (Jurnal Pengembangan Rekayasa dan Teknologi, 2017)
Chayote (Sechium edule) is a vegetable fruit with nutritional content, rich in minerals and vitamins. The high potassium content in chayote has the potential as a food for high blood pressure reduction, with calcium and vitamin C are quite good. In diversification   processed food products chayote   have not been used as a many processed product, usually chayote use as side dish vegetables or   processed as a sweets. Leather is a type of sweets in a sheet, generally made from fruits raw materials, chayote can be used as an alternative material for leather because chayote has a pectin content similar as a fruits, which chayote can be used as a substitute of fruits   in the processed of fruit leather. The research aims is to determine the effect of differences in sugar and CMC concentrations to the physical, chemical and organoleptic properties of chayote leather. Experiment design used a Factorial with Randomized Complete Block Design (RCBD) in 2 factors, first factor is a sugar concentration with 3 levels and second factor of CMC concentration with 2 levels. The First factor of sugar concentration G1 = 5% G2 = 10% G3 = 15%. The second factor of CMC concentration C1 = 0.5% C2 = 1%, repeated 3 times. The variables observed were,tensil strength, content of   moisture, sugar, fiber, potassium, calcium, vitamin C and organoleptics test on elasticity, preference for fruit leather of chayote.The analysis results, there are an influences of   concentrations sugar and CMC on the content of water, sugar, fiber, potassium and calcium but does not affect the tensil strength, vitamin C and panelist preferences on the texture and delight of chayote leather. Interactions occur between sugar and CMC concentrations to  content of potassium and calcium The best chayote leather is the leather with 15% sugar concentration and 1% CMC with characteristics of elasticity in 21,34 N, 12.59% water content, 37,392% sugar content, 4,049% fiber, potassium 207,71 mg/100g, calcium 19,5 mg/100g, vitamin C 7,14 mg / 100g, according to the panelist assessment that chayote leather are chewy and delight with concentration of 10% sugar and 0.5% CMC.
Keywords: chayote; leather; sugar CMC